2021
DOI: 10.1057/s41599-021-00708-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mindfulness outcomes: a moderated mediation analysis of high-performance work systems

Abstract: The purpose of the study was to explain the possible outcomes of mindfulness. The research studied the relationship between mindfulness and employee voice behaviour, affective commitment, job satisfaction, and burnout. The research added one contextual variable, high-performance work system, as a moderator. The sample of the study was faculty members of higher education (management) schools. The sample size was 1092 faculty members. Moderated mediation analysis was used to analyse the data and understand the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 104 publications
(159 reference statements)
1
4
0
Order By: Relevance
“…It can happen because health workers have been tested mentally and psychologically for two years during the Covid-19 period from early 2020 to 2022. This opinion is in line with previous research (Jha, 2021); (Shahbaz & Parker, 2021); (Lyddy et al, 2021). In addition, the well-being and resilience of health workers are high because of the role of the government in providing a sense of security to workers by providing vaccines simultaneously.…”
Section: Discussionsupporting
confidence: 90%
“…It can happen because health workers have been tested mentally and psychologically for two years during the Covid-19 period from early 2020 to 2022. This opinion is in line with previous research (Jha, 2021); (Shahbaz & Parker, 2021); (Lyddy et al, 2021). In addition, the well-being and resilience of health workers are high because of the role of the government in providing a sense of security to workers by providing vaccines simultaneously.…”
Section: Discussionsupporting
confidence: 90%
“…It is suggested that acceptance represents how present-moment awareness is practiced, devoid of judgement, adopting a new attitude of acceptance, openness, and even compassion toward one's experience [40]. Jha indicated that mindfulness impacted job satisfaction and affective commitment positively via employee behavior [41]. In addition, Ngo et al reported that mindfulness has a positive direct impact on job performance and an indirect impact via the creative process's engagement and employee creativity [42].…”
Section: Mindfulnessmentioning
confidence: 99%
“…Numerous researchers from all corners of the globe have looked at the correlation between electricity use and economic growth. In a recent study, Jha (2021) utilized the same technique as Jumbe (2004) and found that the increase in GDP has an effect on the amount of electricity used as well as employment in the short term. However, Bozkaya et al (2022) found a mixed relationship between energy consumption and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Another paper from Jha (2021) looks at the link between GDP, export and power usage for a selection of Middle Eastern nations. When looking at the whole panel, we discover statistically significant feedback effects between some of these components.…”
Section: Introductionmentioning
confidence: 99%